2012
DOI: 10.3168/jds.2011-4603
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vaginoscopy for the diagnosis of clinical endometritis in dairy cows

Abstract: The objective of the study was to evaluate the visual assessment of vaginal discharge by vaginoscopy for the diagnosis of clinical endometritis (CE) in dairy cows. In an in vivo trial, inter- and intraobserver repeatability of vaginoscopic examination (VE) was determined and the effect of transrectal palpation and experience of the investigator evaluated. Holstein-Friesian cows (n=380) were examined by vaginoscopy between 21 and 27 d in milk by 3 investigators twice. Vaginal discharge was categorized on a 4-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 19 publications
(44 reference statements)
5
53
0
Order By: Relevance
“…The vaginal discharge scoring system is based on large-scale studies which have shown, that the diagnosis of pus in the vaginal discharge is related to impaired fertility (LeBlanc et al, 2002). Vaginoscopic examination for the detection of pus in the vagina is not only widely accepted in science but also in veterinary practice to distinguish healthy from diseased cows (Leutert et al, 2012). The incidence of different VDS diagnosed in this study is in line with findings from other studies (Pleticha et al, 2009;Leutert et al, 2012;Wagener et al, 2014b).…”
Section: Othe Rssupporting
confidence: 87%
See 1 more Smart Citation
“…The vaginal discharge scoring system is based on large-scale studies which have shown, that the diagnosis of pus in the vaginal discharge is related to impaired fertility (LeBlanc et al, 2002). Vaginoscopic examination for the detection of pus in the vagina is not only widely accepted in science but also in veterinary practice to distinguish healthy from diseased cows (Leutert et al, 2012). The incidence of different VDS diagnosed in this study is in line with findings from other studies (Pleticha et al, 2009;Leutert et al, 2012;Wagener et al, 2014b).…”
Section: Othe Rssupporting
confidence: 87%
“…of vaginal discharge usually diagnosed from day 21 to 26 postpartum (LeBlanc et al, 2002;Williams et al, 2005;Sheldon et al, 2009;Leutert et al, 2012). Monitoring changes in the bacterial composition of the uterine fluid before the appearance of clinical signs of a disease is crucial not only for a critical interpretation of clinical findings but also for the development of optimal prevention and intervention strategies (Madoz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Barlund et al [6] suggested that uterine cytology is the most reliable method for diagnosing CE in cattle. In veterinary practice, vaginoscopy, the Metricheck device, or the gloved hand are frequently used methods to diagnose CE [7][8][9]. In contrast to the clear definition of CE by Sheldon et al [2], the definition of subclinical endometritis (SE) is still under discussion.…”
Section: Introductionmentioning
confidence: 98%
“…Discharges can be collected and visually examined either by a gloved hand, the Metricheck® device or vaginoscopy (McDougall et al, 2007, Leutert et al, 2012. Based on the discharge characteristics (colour), the discharge obtained is given a score from 0 to 3 based on the amount of pus that the discharge contains.…”
Section: Non-invasive Uterine Assessment Of Endometrial Receptivitymentioning
confidence: 99%